1994
DOI: 10.1111/j.1096-3642.1994.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and ecological remarks on boring sponges (Clionidae) from the Straits of Gibraltar (southern Spain): tentative bioindicators?

Abstract: An important programme of biomonitoring along the coast of Algeciras Bay (Straits of Gibraltar) has allowed us tentatively to consider six species of boring sponges of the genus Cliona as biological indicators: Cliona celata, C. viridis, C. rhodensis, C. vermifera, C. schmidti and C. vastifica. The taxonomy and distribution of these species have been considered in this paper. Ecological observations have permitted us to identify some important characteristics of their habitat on the basis of local environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 6 publications
3
27
0
1
Order By: Relevance
“…If reduced coral calcification is caused by increased nutrient levels, then bioeroding sponges are likely to proliferate, regardless of the substrate conditions. Previous studies have shown that bioeroding sponge distribution densities increase with higher nutrient concentrations (Muricy, 1991; Cuet & Naim, 1992; Carballo et al , 1994; Holmes, 1997, 2000; Holmes et al , 2000). Coincidentally, erosion rates will rise and can strongly affect areas of stressed and weakened reefs (Rose & Risk, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…If reduced coral calcification is caused by increased nutrient levels, then bioeroding sponges are likely to proliferate, regardless of the substrate conditions. Previous studies have shown that bioeroding sponge distribution densities increase with higher nutrient concentrations (Muricy, 1991; Cuet & Naim, 1992; Carballo et al , 1994; Holmes, 1997, 2000; Holmes et al , 2000). Coincidentally, erosion rates will rise and can strongly affect areas of stressed and weakened reefs (Rose & Risk, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…Another aspect to be considered is that traditional taxonomy has resulted in the assumption of some widely distributed cosmopolitan species, based on synonymisations actually due to the lack of discrimination tools with high resolution power. In particular, although P. vastifica is still considered a cosmopolitan, its actual distribution seems to be more limited, as some authors have shown large variation in diagnostic characters on a wide geographical scale, or have even revalidated species names previously synonymised with P. vastifica (Carballo et al 1994;Rosell and Uriz 2002;Rützler 1973;Rützler and Stone 1986). For instance, Carballo et al (2004) resurrected Pione mazatlanensis, rejecting the synonymy with P. vastifica for the Pacific records and proposing to consider all species records from the Pacific Ocean as P. mazatlanensis.…”
Section: Discussionmentioning
confidence: 95%
“…3); microxeas are microspined and bent in the middle. Microspined microrhabd shape is reported to vary from straight to S-or W-shaped, depending on the locality and depth (Calcinai et al 2000;Carballo et al 1994;Rosell and Uriz 2002;Rützler 1973Rützler , 2002a. Although some encrusting specimens from the Red Sea were tentatively identified as P. cf.…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Clionaid sponges have been the subject of several studies in different parts of the world: the Atlantic–Mediterranean province (Volz, 1939; Rützler, 1973; Rützler & Bromley, 1981; Cruz & Bacallado, 1983; Carballo, Sánchez‐Moyano & García Gómez, 1994; Rosel & Uriz, 2002), the Caribbean (Pang, 1973; Rützler, 1974; Rützler, 2002b), North America (Old, 1941; Wells, 1959), the Indian Ocean (Thomas, 1972), and the central Pacific (de Laubenfels, 1954; Schönberg, 2000). However, in spite of the high diversity of clionaid species described in various locations worldwide, no study has ever been devoted entirely to the systematics of burrowing sponges in any single area of the tropical eastern Pacific.…”
Section: Introductionmentioning
confidence: 99%